Out at Work - Anderson, Kelly; Gold, Tami (United States, 1996)
In 1992 Cheryl Summerville, a cook at a Cracker Barrel restaurant outside Atlanta, received a termination paper stating that she was fired for "failing to demonstrate normal heterosexual values." She was shocked to discover that in more than 40 American states it was legal to fire workers simply because of their sexual orientation. “Out at Work” chronicles the stories of a cook, a car mechanic and a librarian as they seek workplace safety, job security and benefits for gay and lesbian workers.
Soros Documentary Fund
Soros Documentary Fund
Keywords: Documentary films